Perancangan Alat Untuk Optimalisasi Pemakaian Energi Listrik untuk Rumah Tinggal Hemat Energi - charles pangaribuan; iwan setiawan (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2018)
Abstract— The use of electrical energy in houses sometimes not optimal and inefficient, because during the houses the have been left by the owner sometimes tedapat the lights or an electrical device that there was really no need operated but still operating, this is what lead to the use of electrical energy vain.To address this so perlulah made a an electronic device that beneficial to control the use of electrical energy home live that devices electricity unnecessary functioned can be made inactive by a device that fitted. A device that made is software of programming c language adjusted with the regulation discharging electricity energy planned and will be upload into device microcontroller electrical Circuit. This Microcontroller also have relay, keypad and other devices supporting from apparatus produces by results according to which planned namely device electricity can active or inactive at the device electicity made this is very effective used in building with installation that uses electric power large